On The Economic Value of Repeated Interactions Under Adverse Selection - Lorenzo Rocco; Ottorino Chillem (Fondazione Eni Enrico Mattei (FEEM), 2006)
The paper studies, in a repeated interaction setting, how the presence of cooperative agents in a heterogeneous community organized in groups affects efficiency and group stability. The paper expands on existing literature by assuming that each type can profitably mimic other types. It is shown that such enlargement of profitable options prevents group stabilization in the single group case. Stabilization can be obtained with many groups, but its driver is not the efficiency gain due to the presence of cooperative individuals. Rather, stabilization is the result of free riding opportunities.
Keywords: D64; D71; D82; 330; Adverse Selection; Group Stability; Altruism; Adverse Selektion; Kollektives Handeln; Altruismus; Theorie